When the Minimum Wage Bites Back: Quantile Treatment Effects of a Sectoral Minimum Wage in Germany - Terry Gregory (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
In this study we investigate the minimum wage (MW) effects for a German sub-construction sector where the MW bites extraordinary hard by international standards. Within a quasi-experiment we estimate the Quantile Treatment Effects of the MW on the conditional and unconditional distribution of earnings. For Eastern Germany, the results indicate significant real (nominal) wage increases that ripple up to about the 0.6th quantile. However, the MW also led to declining real wages (stagnating nominal wages) among upper-decile workers, thus reducing the average pay reward for high-skilled labour in the sector. We provide evidence that a rising labour cost burden for firms together with an increased bargaining power of employers over workers still employed in the sector led to wage moderation at the upper decile, particularly among smaller East German firms. Overall this paper demonstrates how a MW geared towards the lower rank may render unexpected side effects for other workers located higher up in the wage distribution and who are mostly assumed to be unaffected by such policy interventions.
Keywords: J08; J31; C21; 330